Pendampingan Cara Membuat Iklan pada Usaha Keripik Singkong Ibu Imah Rosyidah - Iskandar Zulkarnain; Hestu Nugroho Warasto; Ibnu Sina (Indonesian Journal of Society Engagement, 2022)
The development of the advertising world at this time is increasingly rapid and supported by the growth of print media and the number of television stations (electronic media) which continues to increase, making companies have to be selective in making advertisements to support their sales. Appropriate and efficient marketing and promotion strategies are needed to build a brand image so that the products offered are embedded in the minds of consumers. To see the relationship between advertising and the brand image of the Cassava Chips Production Center with purchasing decisions, the research will be conducted in Gunung Sindur, Bogor, a business owned by Mrs. Imah Rosyidah. The selection of the object of research on Mrs. Imah's Cassava Chips in Gunung Sindur was due to the growing interest in cassava chips in the Gunung Sindur area and its surroundings. The Cassava Chips Production Center, Ibu Imah, is a mini-business that sells various flavors of cassava chips. Consumers who will become customers of this production certainly need comfort. Consumer purchasing decisions to buy cassava chips that they want to consume, when they have a tendency to like both the endorser model and the functions and benefits of the cassava chips themselves. The cassava chips advertisement is one of the advertisements that is planned to be displayed in both print and electronic mass media. Usually, the product advertisement displays an influential figure (Influencer) which aims to attract consumers, especially teenagers. In this advertisement, how to show the unique taste of cassava chips found in all consumers.